A Scoping Review of Transitions, Stress, and Adaptation Among Emerging Adults. (July 2018) - Hanna, Kathleen M.; Kaiser, Katherine Laux; Brown, Sara G.; Campbell-Grossman, Christie; Fial, Alissa; Ford, Amy; Hudson, Diane B.; Keating-Lefler, Rebecca; Keeler, Heidi; Moore, Tiffany A.; Nelson, Audrey E.; Pelish, Peggy; et al.
Abstract : This scoping review examined research on transitions among emerging adults, 18- to 30-year-olds, to identify designs, populations, frameworks, transition types, and transition outcomes. A librarian conducted the search, yielding 2067 articles. Using predefined criteria, teams screened abstracts and reviewed articles, with 82% to 100% interrater agreement. Data from the final 160 articles were placed in evidence tables and summarized. Most frequently, the studies had exploratory-descriptive designs (69%), nondiagnosed samples (58%), no theoretical frameworks (58%), developmental transitions (34%), and health-related behavior outcomes (34%). This transition research is in an early stage of knowledge development and would benefit from further theory development.